Enhanced performance in organic photovoltaic devices with a KMnO4 solution treated indium tin oxide anode modification - 杨倩倩 赵谡玲 徐征 张福俊 闫光 孔超 樊星 张妍斐 徐叙瑢 (中国物理B：英文版, 2012)
The properties of poly（3-hexylthiophene）：（6,6）-phenyl C61 butyric acid methyl ester （P3HT：PCBM） organic pho- tovoltaic devices （OPVs） with an indium tin oxide （ITO） anode treated by a KMnO4 solution are investigated. The optimized KMnO4 solution has a concentration of 50 rag/L, and ITO is treated for 15 min. The modification of ITO anode results in an enhancement of the power conversion efficiency （PCE） of the device, which is responsible for the increase of the photocurrent. The performance enhancement is attributed to the work function modification of the ITO substrate through the strong oxygenation of KMnO4, and then the charge collection efficiency is improved.